A unifying framework for specifying DEVS parallel and distributed simulation architectures. (November 2013) - Adegoke, Adedoyin; Togo, Hamidou; Traoré, Mamadou K
DEVS (Discrete Event System Specification) is an approach in the area of modeling and simulation that provides a means of specifying dynamic systems. A variety of DEVS tools have been implemented without a standard developmental guideline across the board, consequently revealing a lack of central frameworks for integrating heterogeneous DEVS simulators. When implementing a DEVS Simulator there are salient concepts that are intuitively defined, such as how events should be processed, what simulation architecture to use, what existing procedures (set of rules/algorithm) can be used, what should be the organizational architecture and so on. The aim of this paper is to propose a theoretical guide in building a DEVS distributed simulation as well as a formalization of underlying concepts to allow symbolic reasoning and automated code synthesis. From a review of existing implementation approaches, we propose a taxonomy of the identified concepts, including some formal definitions as they constitute the essential building blocks of performing Parallel Discrete-Event Simulation by utilizing DEVS. The contribution of this taxonomy and its impact as a unifying framework is that it provides a more systematic understanding of the process of constructing a DEVS simulator. Also, it offers an abstract way for integrating different and heterogeneous DEVS implementation strategies and thus can serve as a contribution to the on-going DEVS standardization efforts.